2017
DOI: 10.3390/nu9040322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Carbohydrate Diet on Metabolic Parameters in Patients with Type 2 Diabetes

Abstract: In patients with type 2 diabetes mellitus (T2DM), whether dietary carbohydrates have beneficial or detrimental effects on cardiometabolic risk factors has drawn attention. Although a high-carbohydrate (HC) diet and a low-carbohydrate (LC) diet have gained popularity for several decades, there is scarce review focusing on the effects of HC diet on glucose, lipids and body weight in patients with T2DM. In this review, we examined recently-published literature on the effects of HC diets on metabolic parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 96 publications
1
78
0
5
Order By: Relevance
“…Previous study suggested that the magnitude of postprandial responses to mixed meals depended largely on the total amount of fat and carbohydrates intakes 1,5,6 .The American Diabetes Association (ADA) recommends monitoring carbohydrate intake to achieve better glycemic control in patients with type 2 diabetes, which is based on studies showing reduced postprandial glucose and triglyceride responses in individuals consuming HF-LC diets [34][35][36] . However, previous systematic reviews discussed the effects of HF-LC and LF-HC diets on metabolic risk factors and showed inconsistent results 5,7,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous study suggested that the magnitude of postprandial responses to mixed meals depended largely on the total amount of fat and carbohydrates intakes 1,5,6 .The American Diabetes Association (ADA) recommends monitoring carbohydrate intake to achieve better glycemic control in patients with type 2 diabetes, which is based on studies showing reduced postprandial glucose and triglyceride responses in individuals consuming HF-LC diets [34][35][36] . However, previous systematic reviews discussed the effects of HF-LC and LF-HC diets on metabolic risk factors and showed inconsistent results 5,7,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Fiber has been known to have an effect on improve lipid profile and a diet rich in fiber with a low glycemic index (GI)/low glycemic load (GL) may be recommendable in patients with T2DM [18]. Eating at least 22 g/day fiber may reduce total cholesterol and LDL in healthy premenopausal women, and estradiol may slightly reduce the effect [19].…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini juga sesuai dengan penelitian sebelumnya yang melihat hubungan konsumsi karbohidrat dan serat terhadap kadar glukosa darah. (28) Kadar insulin post-test pada penelitian ini, tidak memiliki perbedaan yang bermakna antar kelompok. Pada penelitian ini kadar insulin masing-masing kelompok normal yaitu antara 0,3-1,4 ng/ml.…”
Section: Pembahasanunclassified